Effect of cobalt laurate on the photo-degradation of high density polyethylene - Abdul Hisham, Ruslan (2009)
Plastics nowadays become something very needful in our packaging industry and its roles in our daily activities are irreplaceable. Plastics help make our life easier and better without any doubt. Plastics are polymer and it takes thousand of time to degrade to the environment. Plastic can degrade to the environment by several methods and photo-degradation is one of them. A common photo degradation reaction is oxidation. Then, oxidation agent that use in this research is cobalt laurate. There are 2 reactions involve in production of cobalt laurate. First reaction is sodium hydroxide with lauric acid, and then continues with cobalt chloride after that. The properties of cobalt laurate were measure like density, solubility, melting point and degradation point to analyze. To study the degradation process the polymer type high density polyethylene is used and it was mixed with cobalt laurate as the oxidation agent. The sample was produced by plastic injection molding. The amount of cobalt laurate in the sample is verified to study their effect on the degradation process. The sample was exposed to the sun light under normal and natural environment condition for two weeks to undergo the photo-degradation process. In this process, the sample will absorb the energy in the form of light to break the chain and bonding among polymer. To ensure the photo-degradation is taken place in the sample, it can reveal by determine differentiation and change in mechanical properties of sample before and after the photo-degradation. The mechanical properties are mass, density, tensile strength, elongation break and surface morphology. After this research is done, the conclusion is the degradation of polymer is faster as the amount of cobalt laurate in the sample increase.